Analysis of Current Differential Protection Considering Rated Capacity of Inverter-Interfaced Renewable Plant - Zhang, Hao; Li, Zhongqing; Liu, Sumei; Wang, Danfeng; Dou, Xuewei (Frontiers in Energy Research, 2022)
With the increasing capacity of grid-connected renewable energy power plants (REPPs), the fault current characteristics are remarkably altered. The limited amplitude and controlled initial phase angle of REPPs’ short-circuit current become highlighted. As a result, the differential current is no longer greater than restraint current on both sides of the protected devices when a fault occurs. It may lead to mal-operation of the current differential protection which is used widely. It is necessary to demonstrate the cause-and-effect relationship between REPPs’ rated capacity and the protection adaptability. To solve this problem, the relationship between the rated capacity of inverter-interfaced REPP (IIREPP) and fault current amplitude as well as its initial phase angle is deduced firstly based on the IIREPPs’ fault behaviors. Further, by analyzing the influence of different rated capacity of REPPs on the ratio of operate-to-restraint current, the analytical expression of the IIREPP’s maximum rated capacity is deduced, which is suitable for analyzing the adaptability of differential protection. Finally, the simulation tests were carried out based on PSCAD/EMTDC. The test results show that the aforementioned expression is effective for evaluating the adaptability of current differential protection.